Optimization of cereal-legume blend ratio to enhance the nutritional quality and functional property of complementary food - Walle, Helen; Moges, Demewez (Ethiopian Journal of Science and Technology, 2025)
This study investigated the effect of different cereal-legume blending ratios on nutritional quality and functional property of different blends. The legumes and steeped cereals were cleaned, minimally roasted, dehulled, milled and sifted separately. A single-factor experiment with three levels of the factor (cereal: legume ratio 85:15, 75:25 and 65:35 coded as B1, B2 and B3, respectively) with two replications were used to conduct the experiment. The collected data were subjected to analysis of variance using SPSS statistical software and compared with the recommended values for the age group of 6-24 months. Mean separation result showed that protein, fat, energy, crude fibre and ash contents were significantly (p<0.05) different among the blends where B3 revealed higher values. Protein contents of B2 and B3, ash and fiber content of the three blends, as well as energy value of B3 were within the recommended levels. However, none of the blends met the recommended fat content. Calcium, zinc and iron content of the blends increase as the proportion of legumes increase, but only the iron value was within the recommended level. The molar ratio of phytate and the three minerals were within the recommended value for better absorption. Water solubility index increased as the proportion of legume increased from 15% to 25% then decreased as legume increased to 35%. B1 revealed significantly higher viscosity values (248.43±3.35cP) and viscosity decrease as the proportion of legume increased. Based on 10 nutritional and functional criteria, B3 possess the most desirable among the studied blends.